Contrast monitoring techniques in CT pulmonary angiography: An important and underappreciated contributor to breast dose. Issue 86 (January 2017) - Mitchell, D.P.; Rowan, M.; Loughman, E.; Ridge, C.A.; MacMahon, P.J.
Abstract: Objective: The aims of our study were to evaluate the contribution of contrast-monitoring techniques to breast dose in pregnant and non-pregnant women, and to investigate the effect of a reduced peak kilovoltage (kV) monitoring scan protocol on breast dose and Computed Tomography Pulmonary Angiography (CTPA) diagnostic quality. Materials and methods: Single center retrospective study of 221 female patients undergoing a reduced kV 80 kV contrast-monitoring CTPA protocol compared to 281 patients using the conventional 120 kV contrast-monitoring protocol (Siemens Somatom Definition AS + ). 99 pregnant patients analyzed separately. ImPACT dosimetry software was used to calculate dose. Group subsets were evaluated to assess CTPA diagnostic quality. Results: The contrast-monitoring component of a CTPA study constituted 27% of the overall breast dose when using a standard 120 kV protocol compared to only 7% of the overall breast dose in the 80 kV study group. The dose to the breast from the contrast-monitoring component alone was reduced by 79% in the non-pregnant patients (0.36mGy ± 0.37 versus 1.7mGy ± 1.02; p < 0.001), and by 88% in the pregnant population (0.25 mGy ± 0.67 versus 2.24mGy ± 1.61; p < 0.001). There was no statistical difference in CTPA diagnostic quality or timing. Conclusion: Despite a short scan length and relatively small DLP, contrast-monitoring techniques (test-bolus or bolus-tracked) set at 120 kV can account for 27% of the overall breast dose accrued from a CTPA study. By decreasing the kilovoltage of the contrast-monitoring component, a significant reduction in breast dose for pregnant and non-pregnant female patients can be achieved without affecting CTPA quality or timing.